High TRGV 9 Subfamily Expression Marks an Improved Overall Survival in Patients With Acute Myeloid Leukemia - Kong, Xueting; Zheng, Jiamian; Liu, Xiaxin; Wang, Wandi; Jiang, Xuan; Chen, Jie; Lai, Jing; Jin, Zhenyi; Wu, Xiuli (Frontiers in Immunology, 2022)
Background Heterogeneous T cells in acute myeloid leukemia (AML) have the combinatorial variety generated by different T cell receptors (TCRs). γδ T cells are a distinct subgroup of T cells containing TCRγ (TRGV) and TCRδ (TRDV) subfamilies with diverse structural and functional heterogeneity. Our previous study showed that clonally expanded TRDV T cells might benefit the immune response directed against AML. However, the features of the TRGV repertoire in AML remain unknown. To fully characterize the features of γδ T cells, we analyzed the distribution and clonality of TRGV I-III subfamilies (TRGV II is also termed TRVG 9), the proportions of γδ T cell subsets, and their effects on the overall survival (OS) of patients with AML. Methods In this study, the complementarity-determining region 3 (CDR3) size of TRGV subfamilies in γδ T cells of peripheral blood (PB) from de novo AML patients were analyzed by Genescan analysis. Expression levels of TRGV subfamilies were performed by real-time quantitative PCR. The proportions of total γδ T cells and their Vγ9+ Vδ2+ T cells subsets were detected by multicolor flow cytometry assay. We further compared the correlation among the TRGV gene expression levels, the proportion of Vγ9+ Vδ2+ T cells, and OS in AML. Results We first found that the distribution pattern and clonality of TRGV subfamilies were changed. The expression frequencies and gene expression levels of three TRGV subfamilies in AML samples were significantly lower than those in healthy individuals (HIs). Compared with HIs, the proportions of total γδ T cells and Vγ9+ Vδ2+ T cells were also significantly decreased in patients with AML. In addition, patients with AML who had higher expression levels of the TRGV gene and higher proportion of Vγ9+ Vδ2+ T cells showed better OS than their counterparts. Furthermore, high expression levels of TRGV 9 and proportion of Vγ9+ Vδ2+ T cells were identified as independent protective factors for complete remission in patients with AML. Conclusions The restriction of TRGV usage might be related to the preference of usage of γδ T cells. Higher expression of TRGV subfamilies might be associated with better OS in AML. Higher TRGV 9 expression and increased Vγ9+ Vδ2+ T cells subfamilies might indicate a better prognosis in patients with AML.